2007
DOI: 10.1007/s10526-007-9147-4
|View full text |Cite
|
Sign up to set email alerts
|

Cold stored ectoparasitoid of Cydia fruit moths released under different temperature regimes

Abstract: Cold storage of parasitoids to be used in biological control programs is desirable but risky for the performance of the stored parental generation as well as for its offspring. We studied the performance of cold stored and unstored parasitoids after release at different temperature regimes in the laboratory at the level of two subsequent generations in Hyssopus pallidus (Askew) (Hymenoptera: Eulophidae). This gregarious ectoparasitoid is a candidate biocontrol agent of Cydia pomonella L. (Lepidoptera: Tortrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, our study revealed that cold-stored beetles exhibited a significant decline in the three-day average egg hatch rates, which reached nearly zero on days 17–19. Furthermore, we observed that eggs produced by F1 offspring of cold-stored beetles displayed severely reduced hatchability from the onset of oviposition, indicating transgenerational effects ( Hackermann et al, 2008 ). The extent to which the marked increase in unclassified_f_Enterobacteriaceae within the female reproductive tract of cold-stored H. axyridis adults is associated with their poor reproductive performance remains unclear.…”
Section: Discussionmentioning
confidence: 92%
“…However, our study revealed that cold-stored beetles exhibited a significant decline in the three-day average egg hatch rates, which reached nearly zero on days 17–19. Furthermore, we observed that eggs produced by F1 offspring of cold-stored beetles displayed severely reduced hatchability from the onset of oviposition, indicating transgenerational effects ( Hackermann et al, 2008 ). The extent to which the marked increase in unclassified_f_Enterobacteriaceae within the female reproductive tract of cold-stored H. axyridis adults is associated with their poor reproductive performance remains unclear.…”
Section: Discussionmentioning
confidence: 92%
“…; Häckermann et al. ; Colinet and Boivin ). For example, storage of the pupae of Telenomus busseolae (Gahan) (Hymenoptera: Scelionidae) in the eggs of Sesamia nonagrioides (Lefebvre) (Lepidoptera: Noctuidae) at 4°C (60 ± 5% RH) for 1 week had a significant adverse effect on adult emergence, and for 2 weeks, percentage parasitism of host eggs by emerged females was significantly reduced (Bayram et al.…”
Section: Introductionmentioning
confidence: 99%
“…Storage of natural enemies, particularly parasitoids, at suboptimal temperatures can be valuable for increasing their shelf-life, but entails risks of compromised performance of both the stored parental generation and their offspring (Okine et al 1996;H€ ackermann et al 2008;Colinet and Boivin 2011). For example, storage of the pupae of Telenomus busseolae (Gahan) (Hymenoptera: Scelionidae) in the eggs of Sesamia nonagrioides (Lefebvre) (Lepidoptera: Noctuidae) at 4°C (60 AE 5% RH) for 1 week had a significant adverse effect on adult emergence, and for 2 weeks, percentage parasitism of host eggs by emerged females was significantly reduced (Bayram et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For the mymarid wasp, Gonatocerus ashmeadi Girault (Hymenoptera: Mymaridae), cold storage of immature wasps for 40 days even caused 44% female sterility, and tremendous parasitism and fecundity reduction of 70% and 73%, respectively 8 . Moreover, studies showed that some sublethal effects can even be passed to their offsprings, called "transgenerational effects" 9 . For G. ashmeadi, when cold storage of the adult parents was more than 20 d, delayed development, decreased fecundity, reduced longevity, and increased male production were observed in F1 generation 10 .…”
Section: Introductionmentioning
confidence: 99%